Estimativa do início da formação de orvalho em cafezal por meio dos perfis verticais de umidade absoluta do ar - Lino do Nascimento, Fernando José; Tubelis, Antonio (Revista Ceres, 2025)
This work deals with the study of the initiation of dew formation on coffee tree foliar surfaces by the analysis of: a) the sequence of absolute humidity profiles of the air; and, b) the course of values of vertical water vapor flux density obtained by the Pasquil’s equation (7).